2018
DOI: 10.16970/entoted.447218
|View full text |Cite
|
Sign up to set email alerts
|

Mite species of the vegetable crops in Ordu Province with first report of Amblyseius rademacheri Dosse, 1958 (Mesostigmata: Phytoseiidae) in Turkey

Abstract: Turkey has suitable ecological conditions to grow a wide variety of vegetables. This research was conducted to investigate mite species on cultivated vegetables that include bean (Phaseolus vulgaris L.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…A total of 18 mite species belonging to 3 orders, 6 families and 12 genera were identified as follows: seven species of Phytoseiidae, five Tydeidae, two Tetranychidae, two Stigmaeidae, one for each of Iolinidae and Winterschmidtiidae ( Comments: Transeius wainsteini has been recorded in Denmark, Georgia, Germany, Russia, Iran, Slovakia and Turkey (Demite et al, 2017). In Turkey, it was found on Rosa canina L. (Rosales) in Giresun (Faraji et al, 2011), persimmon trees (Akyazı et al, 2016(Akyazı et al, , 2017, vegetables (Soysal and Akyazı, 2018), stone (Altunç and Akyazı, 2019) and pome (Akyol, 2019) fruit trees in Ordu. It was collected among the Panonychus ulmi (Koch) (Trombidiformes: Tetranychidae) and Aceria sp.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 18 mite species belonging to 3 orders, 6 families and 12 genera were identified as follows: seven species of Phytoseiidae, five Tydeidae, two Tetranychidae, two Stigmaeidae, one for each of Iolinidae and Winterschmidtiidae ( Comments: Transeius wainsteini has been recorded in Denmark, Georgia, Germany, Russia, Iran, Slovakia and Turkey (Demite et al, 2017). In Turkey, it was found on Rosa canina L. (Rosales) in Giresun (Faraji et al, 2011), persimmon trees (Akyazı et al, 2016(Akyazı et al, , 2017, vegetables (Soysal and Akyazı, 2018), stone (Altunç and Akyazı, 2019) and pome (Akyol, 2019) fruit trees in Ordu. It was collected among the Panonychus ulmi (Koch) (Trombidiformes: Tetranychidae) and Aceria sp.…”
Section: Resultsmentioning
confidence: 99%
“…Amblyseius andersoni (Chant) Comments: Amblyseius andersoni is a very common predatory mite species which shows distribution in more than thirty countries (Demite et al, 2017). In Turkey, it was reported on different plants by many researchers (Çobanoğlu, 1992;Ecevit, 2003, 2005;Çobanoğlu, 2004;İnal, 2005;Yanar and Ecevit, 2005;Bayram and Çobanoğlu, 2007;Kumral and Kovancı, 2007;Özşişli and Çobanoğlu, 2011;Yeşilayer and Çobanoğlu, 2011;Faraji et al, 2011;Özsayın, 2012;Satar et al, 2013;Kasap et al, 2013;Gençer-Gökçe, 2015;Kumral and Çobanoğlu, 2015a,b;Çobanoğlu and Kumral, 2016;Çobanoğlu and Güldalı, 2017;Akyazı et al, 2017;Soysal and Akyazı, 2018;Altunç and Akyazı, 2019;Çobanoğlu et al, 2020;Döker et al, 2020;Ersin et al, 2020). It was classified as Type III Lifestyle-generalist predators by McMurtry et al (2013).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Amblyseius rademacheri was found together with T. urticae on S. melongena in Turkey (Soysal and Akyazi 2018). In previous studies, it was found on various fruits, weeds, forest trees in association with tetranychid and eriophyid mites (Hajizadeh 2007).…”
Section: Amblyseius Rademacheri Dossementioning
confidence: 86%